Mapping the Multifaceted Patterns of Industrial Districts: A New Empirical Procedure with Application to Italian Data. Issue 8 (2nd August 2016) - Canello, Jacopo; Pavone, Paolo
Abstract : Canello J. and Pavone P. Mapping the multifaceted patterns of industrial districts: a new empirical procedure with application to Italian data, Regional Studies . This paper illustrates an innovative algorithm to map and classify industrial districts. The theoretical framework uses the Sforzi procedure as a basis for the analysis, revising the main criteria proposed by the original approach. The methodology is tested on the 2001 Italian Census of Industry and Services to allow comparison between the two algorithms. The results show the effectiveness of the new method in identifying industrial districts, without causing distortions to the original framework. The classification proposed allows one to discriminate the areas identified by the procedure according to their structural characteristics, contributing to the unveiling of the diversity underlying the industrial district phenomenon.